2021
DOI: 10.14807/ijmp.v12i9.1637
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of lean thinking in education institutions

Abstract: The economy, culture, and social development of countries in the 21st century are directly related to the quality of education. For education to have expected quality and deliver the desired values to their client, many educational institutions are applying Lean management.  Therefore, the paper aimed to explore the Lean implementation in education through a systematic review of papers from the past five years, in English and the Scopus and Web of Science databases. The methodology was developed using the PRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
(104 reference statements)
0
5
0
2
Order By: Relevance
“…In this paper, we suggest a synthetic review of different studies that have implemented the Lean thinking approach in the field of training from the period 2000 to 2023. To do so, we rely mainly on three complementary studies, the first covering the period 2000-2015 [11], the second one focusing on the period from 2016 to 2020 [12], and a complementary study of articles published on the Scopus database from 2020 to 2023.…”
Section: -Analytical Review Of Lean Implementation Studies In Higher ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we suggest a synthetic review of different studies that have implemented the Lean thinking approach in the field of training from the period 2000 to 2023. To do so, we rely mainly on three complementary studies, the first covering the period 2000-2015 [11], the second one focusing on the period from 2016 to 2020 [12], and a complementary study of articles published on the Scopus database from 2020 to 2023.…”
Section: -Analytical Review Of Lean Implementation Studies In Higher ...mentioning
confidence: 99%
“…Our thorough analysis of existing research on Lean implementation has revealed a lack of concrete studies evaluating its impact on the education system processes [11,12]. Previous research has often been theoretical or limited to specific application cases [13][14][15][16].…”
Section: -Introductionmentioning
confidence: 99%
“…In this phase, the authors followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) protocol (Moher et al, 2009;Nascimento et al, 2021;Santos et al, 2020;Silva et al, 2021;Tanaro et al, 2020), which is broadly employed for conducting systematic literature reviews, mainly in the health field (D'Andreamatteo et al, 2015;Hallam and Contreras, 2018;Silva et al, 2022). PRISMA helps to reduce the risks of elaborating incorrect reports and assures a more precise and comprehensive description of systematic Lean healthcare: bibliometric indicators reviews and meta-analysis (Kelendar et al, 2020;Liberati et al, 2009).…”
Section: Data Collection and Article Classificationmentioning
confidence: 99%
“…O setor de educação, que é foco desta pesquisa, começou a receber atenção por volta de 1995 (SILVA et al, 2021) e obteve melhorias no processo de aprendizagem de novos idiomas (YALCIN TILFARLIOGLU; KARAGUCUK, 2019), maior agilidade para encontrar livros e documentos na biblioteca (SUNDER, 2016), redução do índice de reprovação e melhoria no currículo do curso para se adaptar às necessidades do mercado de trabalho (NALLUSAMYA; PUNNA RAOB, 2018).…”
Section: Introductionunclassified